Productivity and employment in APAC economies: A comparison with the EU using firm-level information - Filippo Di Mauro; Minh Duy Hoang; Peter J. Morgan (Asian Development Bank Institute (ADBI), 2021)
This paper provides an overview of productivity development and other related indicators in Asian-Pacific (APAC) countries, with comparisons with the Europe region. We use the seventh vintage firm-level data from the Productivity Research Network in the APAC region and CompNet in Europe for our study. The overall results show that the productivity growth in developed APAC countries (Australia, New Zealand, and the Republic of Korea) is significantly ahead of the growth in developing APAC countries (India and the People's Republic of China) and on par with the EU's growth. There is an ongoing process of bottom firms catching up with top firms in the Republic of Korea and the richest EU countries. Regarding employment and labor skills, employment growth has generally been quite stagnant in all regions. Labor skills, for which we use the wage premium as a proxy, are quite similar across most regions, with the richest EU countries showing a higher premium than the rest. Our test of the productivity−employment link indicates that the size of employment tends to have a greater impact on productivity in APAC countries, while labor skills have greater emphasis in the EU.
Keywords: D24; E24; J21; J24; P52; 330; productivity; firm-level; employment; labor costs; labor skills; wage premium; TFP dispersion; firm concentration; financial constraint